THE RELIGIOUS MODERATION FOR INDONESIA MUSLIM MIDDLE CLASS: CHALLENGES AND SOLUTIONS - Wasisto Raharjo Jati (Balai Penelitian dan Pengembangan Agama Jakarta, 2023)
This research would like to investigate further religious moderation discourse and its counter-discourse challenges in Indonesia. By taking the example of the Indonesian Muslim middle class, the purpose of this study is to reveal why religious moderation still faces obstacles, particularly in the Indonesian Muslim middle class. This study employs critical discourse analysis by collecting data from relevant literature. The results of this study are: 1) Indonesian Muslim middle classes are still uncertain about adopting religious moderation discourse; 2) there are three main contra narrations to mention here, like religious narcissism, blasphemy, and hate speech, that hinder the implementation of religious moderation.